Optical Molecular Imaging Frontiers in Oncology: The Pursuit of Accuracy and Sensitivity. (September 2015) - Wang, Kun; Chi, Chongwei; Hu, Zhenhua; Liu, Muhan; Hui, Hui; Shang, Wenting; Peng, Dong; Zhang, Shuang; Ye, Jinzuo; Liu, Haixiao; Tian, Jie
ABSTRACT: Cutting-edge technologies in optical molecular imaging have ushered in new frontiers in cancer research, clinical translation, and medical practice, as evidenced by recent advances in optical multimodality imaging, Cerenkov luminescence imaging (CLI), and optical image-guided surgeries. New abilities allow in vivo cancer imaging with sensitivity and accuracy that are unprecedented in conventional imaging approaches. The visualization of cellular and molecular behaviors and events within tumors in living subjects is improving our deeper understanding of tumors at a systems level. These advances are being rapidly used to acquire tumor-to-tumor molecular heterogeneity, both dynamically and quantitatively, as well as to achieve more effective therapeutic interventions with the assistance of real-time imaging. In the era of molecular imaging, optical technologies hold great promise to facilitate the development of highly sensitive cancer diagnoses as well as personalized patient treatment—one of the ultimate goals of precision medicine.